Impact of manganese on the production of a biomass associated β-D-glucosidase activity using a thermophilic Bacillus licheniformis strain - Abdulhamid, María Belén (2015)
The b-Glucosidase (EC 3.2.1.21) constitutes a group of well-studied hydrolases. This enzyme catalyzes the hydrolysis of arylglucosides, alkylglucosides, cellobiose, and cellooligosaccharides. The interest in this biocatalyst centers on its roles in the enzymatic hydrolysis of cellulose. The rate of cellulose hydrolysis can be improved by supplementing commercial cellulases with immobilized b-D-glucosidase, which usually has high stability and can be recovered and reused. In addition, for industrial saccharification of cellulosic materials, b-glucosidases from thermophilic bacteria are also of particular interest due to their increased stability. In this work, we study the influence of manganese on the production of a biomass associate b-D-glucosidase activity using a thermophilic Bacillus licheniformis strain. Assays were performed at 45 °C in 500 ml Erlenmeyer containing 200 ml of LB medium supplemented with 0 - 1.0 mM MnCl2 . The b-D-glucosidase activity was also determined at 45 °C using 3.6 mM p-nitrophenyl-b -D-glucopyranoside (Sigma) as substrate. Cells were harvested by centrifugation and washed twice with 100 mM Tris-HCl buffer (pH 7). The pellet was resuspended in the same buffer, and it was directly used as the b-D-glucosidase source. The mixture was shaken at 1000 rpm. Then, the absorbance of the supernatant was measured at 405 nm and the enzyme activity calculated and related to the biomass dry weight. One unit of the enzyme was defined as the amount needed to release 1 µmol p-nitrophenol per min. Thus, dose-response experiments showed that in the presence of 0.3 mM MnCl2 the enzyme production was increased by about 20%. Under this culture condition, a specific activity value of 19.99 U per mg of dry weight was obtaining after 4 h of cultivation. Finally, these results could be of relevance to the bioethanol industry where lignocellulosic material is used as feedstock for fermentation and, which should be treated enzymatically. The use of naturally bound enzymes is an important immobilization technique. This type of biocatalyst system is potentially cost-effective because the biomass can be directly utilized in the treatment.